Trade openness and female-male earnings differentials: Evidence from Indonesia - Maryam Jamielaa (Universitas Islam Indonesia, 2018)
In the past two decades, Indonesia has experienced an increase in total trade and FDI. In the period 2008-2014, there was an increase of FDI volume, which was followed by a widening trend in the female and male earnings gap. This study investigates the impact of trade openness on female-male earnings differentials and how the impact differs across the wage distribution. This thesis used data employment from the National Labor Survey (SAKERNAS) published by Statistics Indonesia and FDI data released by the Investment Coordinating Board (BKPM). Furthermore, after applying the OLS and the Quantile Regression estimation method, it appears that gender wage gap is narrower in low quantile wage distributions than in high quantile distributions. Also, another important finding emerges from the results of provincial income groups, which shows that gender wage differentials are narrower in high-income and middle provinces than in low-income provinces.